Compositionally controlled band gap and photoluminescence of ZnSSe nanofibers by electrospinning1. Issue 24 (28th June 2015) - Chen, Lin-Jer; Lee, Chia-Rong; Chuang, Yu-Ju; Wu, Zhao-Han; Chen, Chienyi
<x xml:space="preserve">Abstract</x> A simple, non-toxic, low-priced, and reproducible manipulation, which meets the standards of green chemistry, is introduced for the synthesis of ZnSxSe1−x nanofibers. ZnSxSe1−x nanofibers have been prepared in the entire composition range from ZnSe to ZnS by using a low-cost wet-chemical method.